Higher Ground : a Memoir of Salvation Found and Lost. - Briggs, Carolyn S., 1955- (Rowman & Littlefield Pub. Group, 2011)
A riveting memoir of one woman's immersion into fundamentalist faith, and her decision twenty years later to leave it all behind. Beautifully written and powerfully told, this memoir is a fascinating look at the nature of faith, and the inspiring story ofone woman's struggle to find her place in the world. Originally published as This Dark World, this book has been adapted into the screenplay Higher Ground, now a film directed by and starring Vera Farmiga. Carolyn Briggs grew up with modestmeans in the Iowa Heartland. Pregnant at seventeen and married to her musician boyfriend, by the age of.